PENGGUNAAN MEDIA SOSIAL INSTAGRAM TRAVASS LIFE SEBAGAI SARANA KOMUNIKASI PEMASARAN ONLINE - Resty Natalia Mboeik; Nani Kurniasari (Bajang Institute, 2025)
The development of social media has shifted marketing communication patterns from one-way to interactive and participatory. Instagram, as a visual-based social media platform, is now widely utilized by businesses as a digital marketing communication tool. This research aims to describe and analyze the use of Instagram by the Travass Life account as an online marketing communication medium and to identify the communication strategies implemented in building relationships with its audience. This study employs a descriptive qualitative method within a constructivist paradigm. Data were obtained through in-depth interviews with the managers of the Travass Life account and its customers. Observations were conducted on the Instagram account @travasslife. The results indicate that Instagram plays a highly strategic role in Travass Life's marketing communication activities. Features such as feed, reels, stories, highlights, and direct messages are utilized optimally to build the brand's visual identity, increase engagement, and facilitate two-way interaction with the audience. The implemented communication strategy consistently follows the AIDA model through compelling, informative, and persuasive visual content. Furthermore, responsive customer service, the use of testimonials and user-generated content, and consistent content management have proven effective in building customer trust and loyalty. This study concludes that Travass Life's use of Instagram as an online marketing communication medium is effective in increasing brand awareness, audience engagement, and sales conversion.